Essays on banking and agricultural finance - Regmi, Madhav (Kansas State University, 2019)
Financing agriculture has been both an opportunity and a challenge for agricultural banks. Portfolio returns on agricultural banks depend on the profitability of agricultural lending. Changes in the agricultural economy and public policies shape that profitability. A downturn in the agricultural sector adversely affects that success. The regulatory environment also influences the structure and performances of agricultural credit market. Competition with the tax-favored Farm Credit System is another for U.S. agricultural banks. The three essays of this dissertation look at these different dimensions of banking competition and financial policies and their potential effects on the commercial agricultural banks. The first essay examines the impact of bank competition on performance and financial stability of agricultural banks using the Reports of Conditional and Income data. A Lerner index is constructed as a measure of market power. A Z-score is used as a measure of bank riskiness. The return on assets, return on equity, agricultural loan volume and proportion of agricultural loans to the total loans are used as performance measures. Results indicate that bank competition has a U-shaped effect on the probability of default, and an inverted U-shaped effect on volume and proportion of agricultural lending. There also exists an evidence of positive but non-linear effects of bank market power on the profitability of agricultural banks. The second essay examines the effects of the Dodd-Frank Wall Street Reform and Consumer Protection Act of 2010 (Dodd-Frank Act) on cost efficiency, returns to scale and productivity growth measures between big banks and small agricultural banks. The Dodd-Frank Act was intended to reduce the too-big-to-fail practices for very large banks (with asset size above $10 billion and above $50 billion). However, it may have affected the performance of relatively small asset sized banks with different lending portfolios. Using the Reports of Conditional and Income data from 2006 to 2016, results indicate that the Dodd-Frank Act increased cost efficiency, decreased merger incentives and encouraged product specialization for banks above the $50 billion asset size. However, these results do not hold for the banks near the $10 billion asset size. The Act reduced agricultural banks' cost efficiency and increased incentives for mergers. In addition, the Dodd-Frank Act has dampened the incentives of agricultural banks to specialize in agricultural lending. Likewise, evidence exists that this act has slowed productivity growth, efficiency and technological change in agricultural banks. Taken together, the Dodd-Frank Act reduced consolidations in very big banks that are subject to the greater oversight but adversely affected U.S. agricultural lending. The third essay identifies the impact of corporate income tax treatment to the Farm Credit System (FCS) on farm debt share and its consequences on borrowing costs for the farm loans. Also, the spillover effects of market share on interest rates on agricultural loans are estimated. This research finds that a 10 percent increase in state (federal) level corporate income tax is associated with 1.76 percent (3.76 percent) increase in FCS total farm debt market share. For a 10 percent rise in the farm credit system's total farm debt market share results in a 0.06 percent increase in the estimated interest rate of total farm debt. Moreover, state level farm financial measures are also crucial in determining the change in market share of farm credit system and interest rate on the agricultural loan. This dissertation makes three contributions in the banking and agricultural finance literature. First, a competition enhancing (reducing) regulation may improve the financial health of agricultural banks as well as their agricultural lending in the more (less) concentrated agricultural banking market. Second, the Dodd-Frank Act has an indirect and adverse impact on agricultural banking though it may have reduced an incentive to merge in big banks. Third, favorable tax treatment for the FCS has adversely affected the market competitiveness of agricultural banks that may have imposed an indirect burden to the farm households through higher interest rates.
Keywords: Banking; Finance; Agriculture; Competition; Regulation; Taxation